A novel biocompatible formate bridged 1D-Cu(ii) coordination polymer induces apoptosis selectively in human lung adenocarcinoma (A549) cells. Issue 6 (28th January 2021) - Usman, Mohammad; Khan, Rais Ahmad; Khan, Mohammad Rashid; Abul Farah, Mohammad; BinSharfan, Ibtisam I.; Alharbi, Walaa; Shaik, Jilani. P.; Parine, Narasimha Reddy; Alsalme, Ali; Tabassum, Sartaj
Abstract : Copper compounds are promising candidates for next-generation metal anticancer drugs. Abstract : Copper compounds are promising candidates for next-generation metal anticancer drugs. Therefore, we synthesized and characterized a formate bridged 1D coordination polymer [Cu(L)(HCOO)2 ] n, (L = 2-methoxy-6-methyl-3-((quinolin-8-ylimino)methyl)chroman-4-ol), PCU1, wherein the Cu(ii ) center adopts a square pyramidal coordination environment with adjacent Cu⋯Cu distances of 5.28 Å. Primarily, in vitro DNA interaction studies revealed a metallopolymer which possesses high DNA binding propensity and cleaves DNA via the oxidative pathway. We further analysed its potential on cancerous cells MCF-7, HeLa, A549, and two non-tumorigenic cells HEK293 and HBE. The selective cytotoxicity potential of PCU1 against A549 cells driven us to examine the mechanistic pathways comprehensively by carrying out various assays viz, cell cycle arrest, Annexin V-FTIC/PI assay, autophagy, intercellular localization, mitochondrial membrane potential 'MMP', antiproliferative assay, and gene expression of TGF-β and MMP-2.